RISK PROCESS MANAGEMENT: A CASE STUDY IN A FINANCIAL INSTITUTION - Martins Mallet, Fernando; Christine Sotsek, Nicolle; Frazon, Aline (Revista Gestão da Produção Operações e Sistemas, 2024)
Purpose: The purpose of this study is to propose a new method for controlling the product "Financial Risk Management" in a multiple bank. The focus is on addressing Model Risk, particularly in the context of financial institutions, where reliance on incorrect statistical models can pose serious problems. Theoretical framework: Model Risk is the possibility of losses due to models with flaws, deficiencies or inadequacies in the development, implementation or use process. Model Risk is considered one of the main problems for financial institutions. With the advancement of technology and the use of more robust models, dependence on incorrect statistical models can cause serious problems for institutions, increasing the need for studies in the area. Methodology/Approach: To conduct the research, the institution's own survey was used, being applied to the analysis of the main financial models built in the last six months in the organization. As a result, the structure of this process was evaluated, action plans and control indicators were proposed, dividing them into the areas of: Data Governance, Systems, Data Quality and Reporting. With this categorization, it was also possible to create a Control Panel for each Area or Department, improving the management necessary to control Risk. Findings: The findings of the study involve the evaluation of the structure of the risk management process, with a particular focus on addressing Model Risk. The research proposes a new method for risk assessment within the context of "Financial Risk Management" in a multiple bank setting. Research, practical & social implications: In terms of research implications, the study contributes by proposing a novel method for controlling financial risk in a banking environment. The practical implication is the potential improvement in risk management processes within financial institutions. Socially, this research may contribute to the overall stability and reliability of financial systems. Originality/ Value: The originality of this study lies in its proposition of a new method for risk assessment within the domain of "Financial Risk Management" in a multiple bank setup. The value of the research is evident in addressing the critical issue of Model Risk, which can have substantial consequences for financial institutions. Keywords: Financial Institution, Financial Risk, Process Management.